Tales from a not-so-happily ever after / 8. - Russell, Nikki; Russell, Erin (Dork diaries ;, 2014)
A bump on the head suffered during gym class causes middle school drama queen Nikki Maxwell to have a crazy dream where all of her acquaintances assume the roles of familiar fairy tale characters.